680NSAID use and ovarian cancer survival. (2nd September 2021) - Majidi, Azam; Na, Renhua; Jordan, Susan; Obermair, Andreas; Webb, Penelope M
Abstract: Background: Observational studies have reported survival benefits associated with non-steroidal anti-inflammatory drugs (NSAIDs), including aspirin, and non-aspirin NSAIDs (NA-NSAIDs), especially new use post-diagnosis, in women with ovarian cancer (OC). Methods: Participants were women aged 18-79 diagnosed with OC in Australia, 2012-2015. Information was gathered through self-completed 3-monthly questionnaires and prescription records. Exposure was defined as any use (NA-NSAIDs/regular-dose aspirin □1/week or daily low-dose aspirin) during the year pre-diagnosis and first year post-diagnosis. We measured overall survival from start of primary treatment (surgery/neoadjuvant chemotherapy) (pre-diagnosis use) or from 12 months after the start of therapy (post-diagnosis) until the earliest of date of death/last follow-up/5 years. Cox proportional hazards regression was used to estimate survival. We also applied inverse-probability of treatment weighting (IPTW), which balances comparison groups regarding potential confounders. Results: We observed improved survival associated with pre-diagnosis use of aspirin/NA-NSAIDs ≥4 days/week (frequent-users) compared to < 1/week (hazard ratio [HR] =0.72, 95% confidence interval [CI]=0.54-0.97). The association was close to null for those who used medications 1-3 days/week. Similarly, we saw a 30-40% improvement in survival associated with post-diagnosis aspirin/NA-NSAID use, again driven by frequent users (HR = 0.61, 95%CI=0.42-0.88). Results were similar when we excluded pre-diagnosis users, restricted to women who received chemotherapy, or assessed cancer-specific and progression-free survival. Results from IPTW models were similar to adjusted models. Conclusions: Our findings suggest aspirin/NA-NSAID use might improve survival in women with OC. Larger cohorts or, preferably, a randomised controlled trial could clarify these findings. Key messages: Use of aspirin/NA-NSAIDs may improve OC survival.